USP18 Mediates Interferon Resistance of Dengue Virus Infection - Ye, Haiyan; Duan, Xiaoqiong; Yao, Min; Kang, Lan; Li, Yujia; Li, Shilin; Li, Bin; Chen, Limin (Frontiers in Microbiology, 2021)
Previous studies demonstrated that dengue virus (DENV) infection developed resistance to type-I interferons (IFNα/β). The underlying mechanism remains unclear. USP18 is a negative regulator of IFNα/β signaling, and its expression level is significantly increased following DENV infection in cell lines and patients' blood. Our previous study revealed that increased USP18 expression contributed to the IFN-α resistance of Hepatitis C Virus (HCV). However, the role of USP18 in DENV replication and resistance to IFN-α is elusive. In this current study, we aimed to explore the role of USP18 in DENV-2 replication and resistance to IFN-α. The level of USP18 was up-regulated by plasmid transfection and down-regulated by siRNA transfection in Hela cells. USP18, IFN-α, IFN-β expression, and DENV-2 replication were monitored by qRT-PCR and Western blot. The activation of the Jak/STAT signaling pathway was assessed at three levels: p-STAT1 /p-STAT2(Western blot), interferon-stimulated response element (ISRE) activity (Dual-luciferase assay), and interferon-stimulated genes (ISGs) expression (qRT-PCR). Our data showed that DENV-2 infection increased USP18 expression in Hela cells. USP18 overexpression promoted DENV-2 replication, while USP18 silence inhibited DENV-2 replication. Silence of USP18 potentiated the anti-DENV-2 activity of IFN-α through activation of the IFN-α-mediated Jak/STAT signaling pathway as shown by increased expression of p-STAT1/p-STAT2, enhanced ISRE activity, and elevated expression of some ISGs. Our data indicated that USP18 induced by DENV-2 infection is a critical host factor utilized by DENV-2 to confer antagonism on IFN-α.